2019
DOI: 10.1021/acs.langmuir.8b03486
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interfacial Gas Enrichment on Controlled Coalescence of Oil Droplets in Water in Microfluidics

Abstract: Interfacial gas enrichment (IGE) of dissolved gases in water is shown to govern the strong attraction between solid hydrophobic surfaces of an atomic force microscopy (AFM) colloidal probe and a solid substrate. However, the role of IGE in controlling the attraction between fluid-fluid interfaces of foam films and emulsion films is difficult to establish by AFM techniques due to the extremely fast coalescence. Here, we applied droplet-based microfluidics to capture the fast coalescence event under the creeping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Most likely the increased viscosity of dodecane, also decreasing the interfacial mobility, led to an increase of coalescence time as suggested by other authors 23,37 . By comparison, Wang et al reported the coalescence time of squalene droplets (eight times the viscosity of dodecane) in the range of 15-60 ms, depending on the concentration of dissolved oxygen 31 . Krebs et al also reported longer coalescence times for increasing viscosities of mineral and silicone oils 23 .…”
Section: Oil Phase and Drop Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Most likely the increased viscosity of dodecane, also decreasing the interfacial mobility, led to an increase of coalescence time as suggested by other authors 23,37 . By comparison, Wang et al reported the coalescence time of squalene droplets (eight times the viscosity of dodecane) in the range of 15-60 ms, depending on the concentration of dissolved oxygen 31 . Krebs et al also reported longer coalescence times for increasing viscosities of mineral and silicone oils 23 .…”
Section: Oil Phase and Drop Sizementioning
confidence: 99%
“…Lin et al used a collision chamber to investigate coalescence of asphaltene stabilized water-in-oil emulsions in the presence of de-emulsifiers 30 , however, they focused on comparing coalescence rates, rather than coalescence times. Finally, a recent paper by Wang et al presented the effect of dissolved oxygen on coalescence kinetics of squalene droplets in water 31 . While the experimental approach is similar to the one presented here, they reported coalescence of only one size class of droplets with far less coalescence times detected.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to just droplet detection, we show that the models can be trained to discriminate inter-droplet interaction morphologies, such as various coalescence events instead of the actual droplets themselves. Measurement of coalescence time is an important topic in the literature concerning emulsions, and several microfluidic techniques have been reported previously [71,73,74,75]. In our previous work [53], we have also reported a microfluidic method for measuring coalescence time.…”
Section: Coalescence Eventsmentioning
confidence: 98%
“…Wang et al [7] discussed the effect of gas enrichment on wetting film, and they found that a gassed system had faster coalescence due to the strong surface force. Besides, there are multiple theories trying to interpret the mechanism of the film evolution.…”
Section: Introductionmentioning
confidence: 99%